A theoretical study for quantum chemical calculations of tungsten tetracarbonyl complexes with tetrylone ligands E(PH3)2 (E = C − Pb): a quest for understanding - Ai Nhung, Nguyen Thi; Phuong Loan, Huynh Thi; Quang, Duong Tuan; Tat, Pham Van (Vietnam Journal of Chemistry, 2015)
Quantum chemical calculations at the BP86 level with various basis sets (SVP, TZVPP) have been carried out for transition metal complexes of carbodiphosphorane analogues (called tetrylones) E(PH3)2 with E = C, Si, Ge, Sn, Pb. The nature of the [W(CO)4-E(PH3)2] (W4-EP2) bonds was analyzed with charge method. The equilibrium structures of the tetrylone complexes W(CO)4-E(PH3)2 exhibit an interesting trend which possess for E = C, Si a trigonal bipyramidal coordination at tungsten where the tetrylone ligand occupies an equatorial position. The heavier homologues with E = Ge, Sn, Pb exhibit a square pyramidal coordination at tungsten where the tetrylone ligand is at a basal position while one phenyl group is found trans to the apical CO group which yields a hexacoordinated tungsten complex. The calculated equilibrium structures of the complexes [(CO)4W-{E(PH3)2}] show that only the carbone ligand C(PH3)2 is bonded head-on to the metal fragment in the adduct W4-CP2 which the bending angle, α, is 180.0° and the heavier homologues W4-SiP2 to W4-PbP2 have side-on bonded ligands E(PH3)2 which the bending angle, α become more acute. The theoretically predicted bond dissociation energies (BDEs) of W4-EP2 system slightly increase from W4-GeP2 (De = 46.1 kcal/mol) to W4-PbP2 (De = 48.5 kcal/mol). The strange trend has been observed for the slighter homologues with E = C, Si which exhibits the largest value BDE 54.1 kcal/mol for W4-CP2 and 50.1 kcal/mol for W4-SiP2. Analysis of the bonding situation shows that the W-E bonds have a significant contribution from (CO)4W←E(PH3)2 π-donation. This is because the energy levels of the π-type donor orbitals of W4-CP2 – W4-SnP2 are higher lying than the σ-type donor orbitals except for W4-PbP2 where the σ donor HOMO is higher in energy than the π-type donor HOMO-2. All complexes [W(CO)4-E(PH3)2] are suitable targets for synthesis which would open up completely new perspectives for experimental researchers.